Rarity of kidney stones in South Africa's black population : studies of urinary macromolecules, crystal matrix extract containing osteopontin, and bone turnover markers in urine and serum from black and white subjects as a key to understanding this paradox - Deppa, Ntsapokazi (Department of Chemistry, 2016)
The work described in this thesis was undertaken to investigate physicochemical, biochemical and physiological factors contributing towards the rarity of kidney stone disease in the South African black population. Healthy, age-matched male subjects from the black and white population groups were recruited for this purpose. In several of the studies, subjects followed a standardized diet and were required to provide 24 hour urine collections. These were analyzed for sodium, potassium, calcium, oxalate, uric acid, citrate, chloride, magnesium, phosphate, sulphate and creatinine using standard laboratory techniques. Urine composition values were used as input data for the calculation of relative supersaturation (RS) values for calcium oxalate (CaOx), calcium phosphate (CaP, or brushite) and uric acid (U A) using the computer programme EQUIL and for the calculation of the Tiselius Risk Index (TRI). CaOx crystallization experiments were performed. These included CaOx metastable limit (MSL) and BONN Risk Index (BRI) determinations, particle formation kinetics, 14 C-oxalate cry stal deposition kinetics and CaOx crystal aggregation and nucleation inhibition. Crystallizati on experiments were also supplemented with scanning electron microscopy (SEM) and zeta potential measurements. Urine compositions, crystallization data and physicochemical risk indices were analyzed statisitically using ANOV A. Several different investigations were undertaken. These included crystallization experiments involving urinary macromolecules from both race groups, crystal matrix extract isolation (with osteopon tin as its major component) from both race groups and its testing for inhibitory capacity in ultrafiltered urine from both race groups. Similar crystallization experiments were conducted with commercially available osteopontin. In addition, a comprehensive trial was conducted in which the ingestion of three sodium salts (sodium chloride, sodium bicarbonate and sodium citrate) was investigated for their effects on urinary risk factors of CaOx stone formation and for their effects on bone turnover markers in urine and in serum. For the biochemical isolation of crystal matrix extract, COD-CME was precipitated in urine from both black and white subjects. The proteins included in COD-CME were detected using sodium dodecyl sulfate polyacryalamide gel electrophoresis (SDS-PAGE). Western Blotting was used for semi-quantitative analysis of OPN v For the trial involving different sodium salts, four experimental protocols were investigated. The four protocols included low NaCl (3 g/day), high NaCl (12 g/day), sodium bicarbonate (6 g/day) and sodium citrate in the form of Citro-Soda (16 g/day). A Latin Square Design was followed for the random assignment of participants to sequences of protocols. The studies on macromolecules showed that those in the urine of black subjects were more potent inhibitors of CaOx crystal deposition and aggregation than those in the urine of white subjects. Isolation and characterization of the crystal matrix extract in COD crystals confirmed that osteopontin is the main intracrystalline protein in the extract. The crystallization experiments performed on the crystal matrix extract isolated from the urine of both race groups demonstrated that the extract isolated from the urine of black subjects was a superior inhibitor of CaOx deposition, growth and aggregation. Crystallization studies performed on commercially available osteopontin in urine from black and white subjects showed that this protein is a more effective inhibitor of CaOx crystal deposition, growth and nucleation in the urine from the former group compared to that from the latter. The studies on supplemental sodium salts demonstrated that the two race groups respond differently to lithogenic and anti-lithogenic dietary challenges. High NaCl protocol resulted in a favourable and counter-intuitive significant decrease in free unbound calcium in samples from black subjects whereas no such change was observed in white subjects. Supplemental sodium bicarbonate and sodium citrate induced favourable decreases in urinary total calcium, urinary ionized calcium, BRI, RS of CaOx, RS of uric acid and RS of brushite, and a favourable increase in urinary citrate and pH in both groups. Interestingly and more importantly, these factors were more prominent in samples from black subjects than those from white subjects. Bone turnover measurements showed that urinary deoxypyridinoline (DPD) levels were lower while serum osteocalcin (OC) levels were higher in blacks than in whites at baseline, but these differences were not statistically significant. Smaller increases in urinary DPD levels after high aCl and sodium bicarbonate and corresponding bigger increases in serum osteocalcin (OC) levels after these protocols (and sodium citrate) in black subjects than in white subjects indicate less bone resorption and higher bone formation, respectively, in the former group. Vl The results presented in this thesis have provided convincing evidence that in the context of CaOx kidney stone formation, several physicochemical, biochemical and physiological factors are different in black and white South African subjects and that these factors are more effective in the former group with respect to providing protective mechanisms against CaOx kidney stone formation